Fruit yield and gas exchange in bell peppers after foliar application of boron, calcium, and stimulate - Zeist A.R. (2018)
© 2018, Sociedade de Olericultura do Brasil. All rights reserved.The objective of this study was to evaluate the effect of the isolated and combined foliar application of boron, calcium, and the plant growth regulator Stimulate on fruit yield and gas exchange in bell peppers. The evaluated treatments were boron, calcium, Stimulate, boron + calcium, boron + Stimulate, calcium + Stimulate, boron + calcium + Stimulate, and control (water). The study was performed in complete randomized block design with three replicates. The applications were performed biweekly on the plant leaves from the beginning of flowering (December 21, 2013) until March 1, 2014. The analyzed gas exchange characteristics were photosynthetic yield, internal CO2 concentration, and transpiration rate. The evaluated agronomic characteristics were number and yield of marketable and non-marketable fruits, and the average mass, volume, and firmness of commercial fruits. The foliar application of boron from the beginning of flowering increased the photosynthetic yield and the yield of marketable fruits cultivated in the field. The foliar application of calcium and Stimulate did not improve gas exchange and fruit yield. The most common effects of boron were an increase in the number of marketable fruits. Moreover, foliar spraying with calcium from the beginning of flowering increased the firmness of commercial fruits.